Two potential probiotic lactobacillus strains isolated from olive microbiota exhibit adhesion and anti-proliferative effects in cancer cell lines. (June 2016) - Saxami, Georgia; Karapetsas, Athanasios; Lamprianidou, Eleftheria; Kotsianidis, Ioannis; Chlichlia, Aikaterini; Tassou, Chrysoula; Zoumpourlis, Vassilis; Galanis, Alex
Highlights: L. pentosus B281 and L. plantarum B282 exhibited strong adherence capacity to Caco-2 cells. Conditioned media of the two strains caused a significant reduction of cancer cell proliferation. A G1 cell cycle arrest and downregulation of specific cyclin genes were recorded. The bacterial inhibitory compounds are thermostable. Abstract: The beneficial effects of two potential probiotic lactobacillus strains, namely Lactobacillus pentosus B281 and L. plantarum B282 were examined and the mechanisms of action were investigated. Quantitative analysis and confocal microscopy showed that both strains exhibited a significant higher adherence to Caco-2 cells in comparison to the reference strain L. casei ATCC 393. Treatment with conditioned media (CM) of the two strains caused significant reduction of cell proliferation, as demonstrated by Sulforhodamine B (SRB) and clonogenic assays. Moreover, the CM of the two strains induced a G1-phase arrest and down-regulation of specific cyclin genes, as indicated by flow cytometry and real-time PCR analysis. To begin elucidating the nature of the bacterial components conveying these responses, the anti-proliferative effect of heat-treated CM was analysed. The anti-proliferative activity of heat-treated CM was similar to the non-heated CM in a time- and dose-dependent manner, indicating the presence of thermostable bioactive compounds.